Bimbingan Kelompok Dengan Media Permainan Ular Tangga Untuk Meningkatkan Motivasi Belajar - Lianasari, Dewi; Purwati, Purwati; Murtiningsih, Murtiningsih (JURNAL KONSELING GUSJIGANG, 2018)
This research aims at investigating 1) the implementation of group counselling; and 2) finding out how it assisted by snake and ladder media successfully improved students’ learning motivation. It employs pre experimental design with type of one group pre test-post test design. 10 out of 27 seventh graders of SMP Negeri 3 Kota Magelang are assigned as the sample. It used random sampling with the scale of learning motivation. The result revealed that as matter of fact, group counseling had been implemented in this school, though it did not optimally perform in solving students’ problems. Hence it was only done incidentally. The statistic calculations using Paired Sample Test showed that t-value= - 5,129 ≤ t-table= - 0,703. In sum Hawas accepted which meant group counseling with snake and ladder media effectively enhanced students’ learning motivation.